Physical activity and reduced risk of fracture in thyroid cancer patients after thyroidectomy — a nationwide cohort study - Kim, Jinyoung; Han, Kyungdo; Jung, Jin-Hyung; Ha, Jeonghoon; Jeong, Chaiho; Heu, Jun-Young; Lee, Se-Won; Lee, Jeongmin; Lim, Yejee; Kim, Mee Kyoung; Kwon, Hyuk-Sang; Song, Ki-Ho; et al. (Frontiers in Endocrinology, 2023)
Objectives: Levothyroxine suppressive therapy following thyroidectomy for thyroid cancer patients is considered as a risk factor for osteoporosis and fragility fractures. We evaluated the association of regular exercise and exercise habit change with fracture risk in adults older than 40 years who underwent thyroidectomy for thyroid cancer.We enrolled the patients who underwent thyroidectomy for thyroid cancer older than 40 years between 2010 and 2016 from the Korean National Health Insurance Service data, and they were followed through 2019. Based on the questionnaire of health examination within 2 years before and after surgery, whether regular exercise once a week was evaluated. The reference group for the statistical analysis was the continuing lack of physical activity group that did not exercise before or after surgery.For fractures newly diagnosed during the follow-up period, univariate and multivariate Cox regression analyses were performed for risk evaluation.We evaluated 74,774 subjects, of whom 2,924 (3.9%) experienced any fractures during a median follow-up of 4.5 years. Compared with the group consistently lack of physical activity, the group that exercised before and after surgery showed a significant decrease in the risk of any fracture, vertebral fracture, and hip fracture: adjusted hazard ratio 0.848 (95% Confidence Interval 0.771-0.932), 0.703 (0.591-0.836), and 0.405 (0.224-0.732), respectively. For vertebral fracture, a significant reduction in fracture risk was confirmed even in patients who started their regular exercise after surgery: adjusted hazard ratio 0.779 (0.648-0.936). The risk reduction for vertebral fractures upon the initiation of exercise was found to be significant in the high-risk groups of patients: women and total thyroidectomy patients.We suggest that maintaining or starting regular exercise after surgery may help prevent fractures in thyroid cancer patients older than 40 years who have undergone thyroidectomy.